Synergistic Protective Effect of Konjac Mannan Oligosaccharides and Bacillus subtilis on Intestinal Epithelial Barrier Dysfunction in Caco-2 Cell Model and Mice Model of Lipopolysaccharide Stimulation - Chen, Lupeng; Zhang, Shuai; Wu, Shi; Ren, Zhuqing; Liu, Guoquan; Wu, Jian (Frontiers in Immunology, 2021)
As the first line of defense against intestinal bacteria and toxins, intestinal epithelial cells are always exposed to bacteria or lipopolysaccharide (LPS), and pathogenic bacteria or LPS can cause intestinal epithelial cell damage. Previous studies have shown that konjac mannan oligosaccharides (KMOS) have a positive effect on maintaining intestinal integrity, and Bacillus subtilis (BS) as a probiotic can promote the barrier effect of the intestine. However, whether KMOS and BS have a synergistic protective effect on the intestines, and the mechanism of their action, is still unknown. In this study, we used the LPS-induced Caco-2 cell injury model and mouse intestinal injury model to study the synergistic effects of KMOS and BS on Caco-2 cell injury and intestinal injury. Our results show that the combined use of KMOS and BS has a synergistic repair effect on Caco-2 cells and mouse intestinal injury, and can enhance the antioxidant function of cells, which is beneficial for the protection of LPS-induced acute injury mouse models.